PERENCANAAN PEMBANGUNAN DAERAH DALAM PENANGGULANGAN KEMISKINAN (Studi tentang Perencanaan Pembangunan Melalui Program Satu Miliyar Satu Kecamatan (SAMISAKE) di Kota Jambi) - Rizalul Fikri (REFORMASI, 2015)
Poverty is a problem that requires countermeasures and systematic approach, integrated and comprehensive to meet the load and meet the basic rights of citizens through the development of an inclusive, equitable and sustainable to achieve a dignified life. To answer the problems of poverty, the Provincial Government Jambi produce a poverty reduction program Satu Milyar satu Kecamatan (SAMISAKE). The program took the form of assistance provided directly from the Government to the public in the form of surgical house, capital assistance, scholarships schools etc. The study is based on the findings of this thesis are: 1) planning is in conformity with the legislation just takes more effort to produce careful planning. It takes the involvement of all stakeholders in the planning process. If seen from the amount of the budget compared with the area, the amount of the budget it is still lacking; 2) Determination of target beneficiaries have been set in legislation, but the lack of data that is valid and up to date lead to less targeted recipients; 3) Should the excess of the underlying implementation of the law, should be able to be supported by the implementation of good management as well. Involving all levels of government in the region is also very important to be able to minimize the obstacles that occur in the field.